Application of The Leading Sector Identification Method in The Portfolio Analysis - Tarczyński, Waldemar Stafan; Tarczyńska-Łuniewska, Małgorzata Ludmiła (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The development of the stock market requires taking into account the impact of many factors. Knowledge of the entire market is a result of research at different levels of aggregation. Referring to sectors, it should be stated that the level of economic development and financial sector shapes the picture of economic and market conditions being a derivative of development level of the entities forming the market. Therefore, the possibility of identification of leading sectors or companies that have the greatest impact on the market becomes significant. This approach is important due to several reasons. One of them is the process of investing in the capital market. Thus, the main objective of the study is to provide methods of identifying the leading sector in the capital market and the use of this information in the procedure of building a portfolio of securities. The study was carried out for the Warsaw Stock Exchange in 2006–2010. Certain information in the field of fundamental factors was utilized in the analysis. Selected factors were used for the construction of the dynamic fundamental power index FPI. This paper proposes a simple method of determining the leading sector. The method takes into account information about the fundamental strengths of companies forming a sector and the number of companies comprising a given sector. Based on this information, a procedure of building a portfolio of securities was proposed. At the beginning of 2011 two types of portfolios were constructed and their effectiveness for 2011–2016 (26 IX) was verified. As a result of the research the hypothesis that selection of securities to portfolio using the leading sector identification method is better than the classical methods of portfolio analysis was proven.